Caffeine and sprint cycling performance: Effects of torque factor and sprint duration - Glaister, M.; Towey, C.; Jeffries, O.; Muniz-Pumares, D.; Foley, P.; McInnes, G. (International Journal of Sports Physiology and Performance, 2019)
Purpose: To investigate the influence of torque factor and sprint duration on the effects of caffeine on sprint cycling performance. Methods: Using a counterbalanced, randomized, double-blind, placebo-controlled design, 13 men completed 9 trials. In trial 1, participants completed a series of 6-s sprints at increasing torque factors to determine the torque factor, for each individual, that elicited the highest (Toptimal) peak power output (PPO). The remaining trials involved all combinations of torque factor (0.8 N/m·kg vs Toptimal), sprint duration (10 s vs 30 s), and supplementation (caffeine [5 mg/kg] vs placebo). Results: There was a significant effect of torque factor on PPO, with higher values at Toptimal (mean difference 168 W; 95% likely range 142-195 W). There was also a significant effect of sprint duration on PPO, with higher values in 10-s sprints (mean difference 52 W; 95% likely range 18-86 W). However, there was no effect of supplementation on PPO (P = .056). Nevertheless, there was a significant torque factor × sprint duration × supplement interaction (P = .036), with post hoc tests revealing that caffeine produced a higher PPO (mean difference 76 W; 95% likely range 19-133 W) when the sprint duration was 10 s and the torque factor was Toptimal. Conclusion: The results of this study show that when torque factor and sprint duration are optimized, to allow participants to express their highest PPO, there is a clear effect of caffeine on sprinting performance.